A Novel Hybrid Spraying Method for Obtaining High Quality Coatings - SZCZUCKA-LASOTA, Bożena; STANIK, Zbigniew; TARASIUK, Wojciech; SIETESKI, Dariusz (Engineering Transactions, 2016)
The aim of this study is to present the development of the hybrid method, and its possible applications, advantages and limitations. The new elaborated method of spraying can be applied for the production of coatings working in an aggressive environment. In the paper, the corrosion-erosion resistance of coatings obtained by the hybrid method is presented. The structure and chemical composition of coatings are obtained by the scanning electron microscopy (SEM). The made samples were subject to cyclic corrosion test in air and at high temperature of 650°C. The changes in mass of samples in time were measured and the curve of the course of corrosion processes was specified. In this paper, the results of abrasion test on T07 stand and erosion tests under a load of 200 g in ambient and elevated temperature are presented. The presented results confirm the correctness of chosen parameters of a new, elaborated and innovative hybrid method.